Lymph and blood vessel architecture in benign and malignant prostatic tissue: lack of lymphangiogenesis in prostate carcinoma assessed with novel lymphatic marker lymphatic vessel endothelial hyaluronan receptor (lyve-1) - Trojan, Lutz; Michel, Maurice Stephan; Rensch, Florian; Jackson, David G.; Alken, Peter; Grobholz, Rainer (The journal of urology, 2004)
Purpose: - - Due to the lack of specific markers the analysis of lymphatic vessel density (LVD) has been almost impossible in the past. We report the novel specific marker for lymphatic endothelium, lymphatic vessel endothelial hyaluronan receptor (LYVE-1), in prostatic, benign prostatic hyperplasia (BPH) and prostate cancer (PCa) tissue. Normal blood vessels were additionally quantified in BPH and PCa. - - Materials and Methods: - - LYVE-1+ lymphatics (LVD) and CD34+ blood vessels were assessed in 20 paraffin sections of BPH and 50 of PCa tissue by immunohistochemistry in a standardized experimental setting. The regions of PCa, periphery of the tumor and nontumorous regions of the PCa specimens, and BPH tissue were evaluated. Double staining was done (LYVE-1/CD34). Acquired data were interrelated and compared to the pathological parameters of the specimens. - - Results: - - Double staining revealed numerous CD34+ blood vessels but only a few LYVE-1+ lymphatic vessels in BPH and PCa sections. Mean LVD ± SD was distinctly lower (0.55 ± 0.93) in PCa tissue than in tumor periphery (2.45 ± 1.93) and nontumorous (3.16 ± 2.23) tissue (p <0.0001). Maximum LVD was observed in BPH (7.17 ± 3.61), which differed markedly from nontumorous areas of PCa specimens (p <0.001). In contrast to LVD, significantly more blood vessels were found in PCa (116.00 ± 39.25) than in BPH (60.30 ± 19.34) tissue (p <0.001). - - Conclusions: - - LYVE-1 is a specific lymphatic endothelial marker in benign and malignant prostate tissues. It is a useful new marker for the investigation of lymphatics. To our knowledge we report the immunohistochemical visualization and quantification of lymphatic vessels in prostatic tissue for the first time. In contrast to the stimulated angiogenesis of blood vessels in PCa, the destruction of lymphatic vessels occurs rather than lymphangiogenesis.